2012
DOI: 10.5101/nbe.v4i2.p58-65
|View full text |Cite
|
Sign up to set email alerts
|

Electrolytic Synthesis and Characterization of Silver Nanopowder

Abstract: This work reports a simple, novel, cost effective and eco-friendly electrolytic synthesis of silver nanoparticles using AgNO 3 as metal precursor. The synthesis rate is much faster than other methods and this approach is suitable for large scale production. They are characterized by XRD, SEM and FT-IR techniques to analyze size, morphology and functional groups. XRD studies reveal a high degree of crystallinity and monophasic Ag nanoparticles.Their particle size is found to be 24 nm and specific surface area (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
79
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(98 citation statements)
references
References 20 publications
18
79
0
1
Order By: Relevance
“…1 Optical density of silver nanoparticles synthesized using P. serratifolia leaf extract 64.69°and 77.62°, corresponding to 111, 200, 220, and 311 planes of the face-centered cubic (fcc) for silver, respectively. This is in agreement with the results obtained by other workers (Martinez-Castanon et al 2008;Parikh et al 2011;Theivasanthi and Alagar 2011). Moreover, few small insignificant impurity peaks were also observed, which may be attributed to other organic substances in reaction mixture.…”
Section: Resultssupporting
confidence: 83%
“…1 Optical density of silver nanoparticles synthesized using P. serratifolia leaf extract 64.69°and 77.62°, corresponding to 111, 200, 220, and 311 planes of the face-centered cubic (fcc) for silver, respectively. This is in agreement with the results obtained by other workers (Martinez-Castanon et al 2008;Parikh et al 2011;Theivasanthi and Alagar 2011). Moreover, few small insignificant impurity peaks were also observed, which may be attributed to other organic substances in reaction mixture.…”
Section: Resultssupporting
confidence: 83%
“…The average dislocation density of lead nanoparticles found to be as 11.1 × 10 14 m -2 . The dislocation density of electrolyzed silver nanoparticles 9.2 × 10 14 m -2 has been noted from our earlier report [28]. It is observed that the sample lead nanoparticles harder than electrolyzed silver nanoparticles.…”
Section: Xrd-dislocation Density and Theoretical Densitymentioning
confidence: 77%
“…The equations for the calculation of lattice constant, particle size, instrumental broadening, dislocation density, theoretical density, crystallinity index, morphology index and specific surface area are in our earlier report [28], presented in other reports as per the references as well as in the supplementary file.…”
Section: Specific Surface Areamentioning
confidence: 99%
See 1 more Smart Citation
“…It is observed that GQDs (point out by yellow font) are attached on the surface of Ag nanoparticles, where the d-spacing planes of Ag and GQDs (marked in white font) can be distinguished. The d-spacing of 0.145 nm corresponds to the (220) plane of silver, 44 and the d-spacing of 0.214 nm corresponds to the (110) plane of GQDs. 41,45 We used the XRD technique to identify the presence of silver and GQDs in the nanocomposites.…”
Section: Results and Discussion Synthesis And Characterization Of Ag-mentioning
confidence: 99%